Tourist Behavior in Helicopter Charter Service Selection in Las Vegas, Nevada, USA - Hopper, Tomas; Hopper, Saranpath; Puriprinya, Kampetchara; Prawatrungrueng, Amornrat; Singsamran, Pornnarong (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study examined tourist behavior in helicopter charter service selection in Las Vegas, Nevada, USA, with three objectives: (1) to describe behavioral characteristics of helicopter charter tourists; (2) to compare behavioral differences across demographic groups (gender, age, income level, and nationality); and (3) to propose evidence-based service development guidelines. An Explanatory Sequential Mixed Methods design was employed, comprising a quantitative phase using a validated Likert-scale questionnaire (n = 400; IOC = 0.87; Cronbach’s α = 0.91) and a qualitative phase involving semi-structured in-depth interviews (n = 30; Inter-rater Reliability = 0.84). Results indicated that the primary market segment consists of affluent male professionals aged 35–55, predominantly using helicopter services for aerial sightseeing at an average expenditure of USD 4,250 per trip. Statistically significant behavioral differences were found across all demographic variables (p < 0.05). Four key service development priorities emerged: enhancing safety standards, developing 4E experience packages, building luxury hotel partnerships, and investing in social proof-driven digital marketing. These findings contribute to the luxury experiential tourism literature and offer actionable implications for operators seeking to deliver differentiated, segment-specific helicopter tourism services.